PEMANFAATAN DAUN SEBAGAI PEMBUNGKUS MAKANAN TRADISIONAL OLEH MASYARAKAT BANGKA (Studi Kasus di Kecamatan Merawang) - Rini Rini; Yulian Fakhrurrozi; Dian Akbarini (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2017)
One of food materials wrappings used are leaves. The leaves are natural and safe material to wrap foods. The use of materials are traditional knowledge is very valuable and including culture wealth. It must be give more attention to perpetuated and developed. This research was taked from April to Desember 2015 in Merawang district Bangka regency. Data colecting tecnic in this research were interview and direct observation, determining informans and location with purposive tecnic. The result of research showed to consist of 12 type from 7 plants family that it’s leaves used as traditional foods wrapping by people Merawang district Bangka regency. Plants species used is Arenga pinnata, Cocos nucifera, Nypa fruticans, Areca cathecu (Arecaceae); Dillenia suffruticosa (Dilleniaceae); Curculigo capitulata (Hypoxidaceae); Musa paradisiaca (Musaceae); Pandanus furcatus, Pandanus tectorius, Pandanus amaryllifolius (Pandanaceae); Bambusa sp. (Poaceae); and Etlingera sp. (Zingiberaceae). Arecaceae family plant is the most plant type is used. The plant type which is often used is banana leaves, namely used to 16 foods type